ABM Proceedings 2014
DOI: 10.5151/1982-9345-24250
|View full text |Cite
|
Sign up to set email alerts
|

Estudo De Inclusões Não-Metálicas Em Aços Durante Tratamento Em Desgaseificador a Vácuo E Início Do Lingotamento Contínuo

Abstract: ResumoO atingimento de limpeza inclusionária está ligado ao entendimento de como cada etapa de processamento de aços influenciam no comportamento inclusionário. Neste estudo, retiraram-se amostras de aço antes e após o tratamento a vácuo e no distribuidor do lingotamento contínuo em uma planta siderúrgica. As amostras foram submetidas à análise via MEV/EDS automatizado e a medições de oxigênio total. O posicionamento da composição química das inclusões varridas em diagramas ternários remetidas à análise de sua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
1
4
0
1
Order By: Relevance
“…In general, it is concluded that Al 2 O 3 inclusions are formed as a result of re-oxidation by air (the effect of the oxidation degree in slag is smaller) and the decrease in temperature during the final step of the steel manufacturing process 9,27,43 . On the other hand, the formation of inclusions of pure spinel (MgO⋅Al 2 O 3 ) is facilitated due to an increase in slag fluidity, which leads to increased MgO erosion of slag line refractories, as well as MgO saturation, which increase the dissolved magnesium in the liquid steel 1,9,10,17,18,[44][45][46][47][48] . Secondary spinel formation by re-oxidation after modification with calcium should also be considered 38,45,47,49,50 .…”
Section: Inclusionary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is concluded that Al 2 O 3 inclusions are formed as a result of re-oxidation by air (the effect of the oxidation degree in slag is smaller) and the decrease in temperature during the final step of the steel manufacturing process 9,27,43 . On the other hand, the formation of inclusions of pure spinel (MgO⋅Al 2 O 3 ) is facilitated due to an increase in slag fluidity, which leads to increased MgO erosion of slag line refractories, as well as MgO saturation, which increase the dissolved magnesium in the liquid steel 1,9,10,17,18,[44][45][46][47][48] . Secondary spinel formation by re-oxidation after modification with calcium should also be considered 38,45,47,49,50 .…”
Section: Inclusionary Analysismentioning
confidence: 99%
“…The disintegration of the aluminate complexes into smaller units results in a decrease in viscosity. According to the studies of Asth 14 and Bartosiaki et al 17,18 , an excess of refractory oxides (CaO and MgO) can increase the viscosity of slags due to the presence of solids (CaO precipitation or CaO rich phases, spinels (MgO•Al 2 O 3 ) and MgO) which are detrimental to the process of nonmetallic inclusion removal. According to Valdez et al 7 , increasing the viscosity of the slag (by the effect of solid phase precipitation) causes a much longer time for the inclusions to be completely removed from liquid steel, and in the case of a low viscosity slag, the particle can be more easily removed through it.…”
Section: Introductionmentioning
confidence: 99%
“…The sampling methodology follows the experimental procedure adopted in previous studies [24][25][26][27][28] . Figure 1 ilustrates the sampling process described.…”
Section: Sampling and Analysis Techniquesmentioning
confidence: 99%
“…As can be seen in Table 1, the Al 2 O 3 , CaO, SiO 2 contents of these slags range between 15-25%, 47-52% and 13-17.6% by mass, respectively. Typical slag compositions for secondary refining of high basicity (2.8-3.6), saturated in CaO and MgO and with high content of alumina 25,36,37 . MgO content in the slag is in the range of 9 to 16 mass%.…”
Section: Effects Of the Slag Chemical Composition On Mgo Content Of Imentioning
confidence: 99%
“…Entretanto, esses procedimentos podem se ternar custosos e interferirem diretamente no processo de produção, gerando custos que só são justificados na produção de aços especiais (que possuem um maior valor agregado), como é o caso da utilização do desgaseificador a vácuo, utilizado em grande parte das siderúrgicas. [13,14,15] Levando em consideração o exposto acima, este trabalho tem por objetivo principal identificar, quantificar e classificar as inclusões presentes nas amostras analisadas, bem como observar se há um padrão de ocorrência das mesmas.…”
Section: Introductionunclassified